PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PEGAWAI PADA DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN SERANG - Angrian Permana; Rani Puspa; Listiawati Listiawati; Wahyudi Wahyudi (Jurnal Ilmiah Manajemen dan Bisnis, 2017)
The variables in this study are Transformational Leadership Style (X1), Work Discipline(X2) and Employee Performance (Y). The purposes of this study are to know the influenceof transformational leadership style on employee performance, work discipline onemployee performance, and influence of transformational leadership style and workdiscipline on employee performance at the Department of Tourism, Youth and Sports ofSerang Regency. This research used questionnaires instrument to 34 employees at theDepartment of Tourism, Youth and Sports Serang Regency. The researcher used a tool,named SPSS 22 to get the result of the data. The researcher used it to get the result ofvalidity, reliability, classic assumption, simple regression, multiple regression, correlation,and hypothesis test. The result showed that the first variable (transformational leadershipstyle) has positive and significant influence on employee performance, the second variable(work discipline) has positive and significant influence on employee performance, and thelast result showed that transformational leadership style and work discipline has positiveand significant influence on employee performance at the Department of Tourism, Youthand Sports Serang Regency